Efektivitas Penggunaan Biji Kelor (Moringa Oleífera, Lam) Sebagai Koagulan Untuk Menurunkan Kadar TDS dan TSS Dalam Limbah Laundry - Ahsanul Hak; Yeti Kurniasih; Husnul Hatimah (Universitas Pendidikan Mandalika Mataram, 2019)
Laundry waste contains detergent which can cause water pollution because itcontains various kinds of substances that can affect various waterparameters, especially such as TDS (total dissolved solids) and TSS (totalsuspended solids). To reduce these parameters is done by the coagulationprocess which is adding moringa seed powder as coagulant. Moringa seedscan work as a coagulant because they contain an active substance, 4-alfa-4-rhamnosyloxy-benzil-isothiocyanate. The coagulation process was carried outby varying several coagulation parameters such as the size of the coagulantpowder (Al (80-100mesh) and A2 (100mesh), stirring speed (slow, medium,and fast), settling time (15, 45 and 75 minutes) and mass ratio to samplevolume (100 mg against 100, 150 and 200 mL) .The samples used in thecoagulation process were taken by grab sampling technique and thedetermination of TDS and TSS levels was carried out by the gravimetricmethod. The data showed the size of moringa seed powder coagulant, stirringspeed, settling time and coagulant mass ratio with sample volume influencethe% decrease in TDS and TSS levels, optimum conditions on coagulantpowder size> 100 mesh, moderate stirring speed, 15 minute deposition timeand coagulant mass ratio to sample volume 1: 1 ( mg / L), where% decreasein TDS is 74.07% from 270000 mg / L to 70000 mg / L and TSS of 82.14%from 56000 mg / L to 10000 mg / L.